2016
DOI: 10.1038/jp.2016.31
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of surfactant replacement therapy for preterm neonates with respiratory distress syndrome in low- and middle-income countries: a systematic review

Abstract: Surfactant replacement therapy (SRT) has been shown to reduce mortality and air leaks in preterm neonates from high-income countries (HICs). The safety and efficacy of SRT in low- and middle- income countries (LMICs) have not been systematically evaluated. The major objectives of this review were to assess the (1) efficacy and safety, and (2) feasibility and cost effectiveness of SRT in LMIC settings. We searched the following databases—MEDLINE, CENTRAL, CINAHL, EMBASE and WHOLIS using the search terms 'surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 50 publications
1
30
0
1
Order By: Relevance
“…SRT is the core of RDS management [4]. In RRR, SRT with nCPAP is safe and efficacious [20] and decreases mortality by 25% [21]. SRT, via less invasive methods, is widely used on a global scale.…”
Section: Rds Management In Rrr Of Ssamentioning
confidence: 99%
“…SRT is the core of RDS management [4]. In RRR, SRT with nCPAP is safe and efficacious [20] and decreases mortality by 25% [21]. SRT, via less invasive methods, is widely used on a global scale.…”
Section: Rds Management In Rrr Of Ssamentioning
confidence: 99%
“…The results in this study have proven that the mortality was very low among premature subjects and majority of them were improved and shifted from ICU which support the study conducted by during 23 and 34 weeks gestational aged premature neonates but it was not agreed by the findings of Sankar et al, (2016) who found no difference in the risk of mortality in one of their randomized control trial. This study divulged that early administration of surfactant plays an important role in the prognosis of premature neonates with surfactant replacement therapy.…”
Section: Resultsmentioning
confidence: 41%
“…Sankar et al in a systematic review of the efficacy and safety of SRT in preterm infants with RDS in low-and middle-income countries have concluded that SRT is safe, effective, and feasible in level III neonatal units and has the potential to decrease mortality. 20 In order for this to be realized, however, solutions to affordability and accessibility of surfactant, mechanical ventilators, CPAP machines, and neonatal intensive care measures would have to be devised.…”
Section: Outcome Of Patients Receiving Surfactant Replacement Therapymentioning
confidence: 99%